2010
DOI: 10.1212/wnl.0b013e3181d1a862
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular interferon beta-1a in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: This study was designed to provide Class I evidence for the safety and efficacy of IM IFNbeta-1a in the treatment of CIDP but has been subsequently classified as Class II due to a >20% patient dropout rate. Thus, this randomized, controlled clinical trial provides Class II evidence of no effect on primary and secondary endpoints of 4 dosage regimens of IM IFNbeta-1a added to IVIg in persons with CIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 24 publications
2
53
0
3
Order By: Relevance
“…Antigenic targets in CIDP have been recently reviewed (Pollard, 2007;Hughes et al, 2010). The therapeutic response of patients with CIDP to plasma exchange strongly suggests that humoral mediators such as antibodies play a role in the pathogenesis of this disease.…”
Section: Antigenic Targets In Cidpmentioning
confidence: 99%
“…Antigenic targets in CIDP have been recently reviewed (Pollard, 2007;Hughes et al, 2010). The therapeutic response of patients with CIDP to plasma exchange strongly suggests that humoral mediators such as antibodies play a role in the pathogenesis of this disease.…”
Section: Antigenic Targets In Cidpmentioning
confidence: 99%
“…It showed an improvement in clinical grading but not in grip strength scores. Then, a large RCT was conducted in 67 patients with IVIGdependent CIDP, followed for 32 weeks, with either 30 or 60 mg of IFN-β1a once or twice weekly [60]. IFN-β1a was not more effective than placebo in reducing the mean dose of IVIG, with 47 % of patients in both groups not needing to restart IVIG after their suspension after 16 weeks of therapy with IFN-β1a.…”
Section: Long-term Therapy For Cidpmentioning
confidence: 99%
“…A negative randomized controlled trial of oral methotrexate 15 mg weekly was reported in CIDP [109]. A recent studied evaluating the effects of intramuscular interferon-beta-1a (Avonex) at low (30 micrograms weekly), intermediate (30 micrograms twice weekly or 60 micrograms weekly) and high dose (60 micrograms twice weekly) on IVIg dose in CIDP did not show a significant benefit [104,105,110]. High dose cyclophosphamide without stem cell rescue can lead to long-term remission with refractory CIDP [97] with improved quality of life [112].…”
Section: Treatmentmentioning
confidence: 99%